MODIFIKASI BENTUK DAN ANALISIS ALIRAN FLUIDA PADA SUATU FUSELAGE KAPAL UDARA - Fadlan Ekadj, Firza
This study is intended to learn some considerations in hull and ski designs on a flying buat, specifically at take-off and landing on sea water with sea state 4 condition. On a hull part, there are parameters which influence performances at take-off and landing on water; spray strip, deadrise angle, the location and the shape of the translating ski. The study is headed toward modification of hull and ski design, therefore the new total drag, which is the sum of drag components of sea water and air, would become better than the former design’s result. Furthermore, the advantage on lift and lift to drag ratio are observed. Therefore, a fluid flow analysis is conducted using sea water and air as mediums. A CFD simulation is conducted on a given fuselage design and modified designs. Then, the new results are analyzed its difference with the former result. The CFD is conducted using ANSYS Fluent using volume of fluid model and k-? RNG turbulent model. . The fuselage geometry modifications include ski location change, deadrise angle change, and thickness change at ski’s rear end. From the CFD analysis, it is seem that the result of the modified geometry is better, but the process of improvement needs to be continued so the result can be optimum.